Mechanistic insights into the iron–sulfur cluster-dependent interaction of the autophagy receptor NCOA4 with the E3 ligase HERC2 - Haobo Liu; Liqiang Shen; Xinyu Gong; Xindi Zhou; Yichao Huang; Yuqian Zhou; Zhenpeng Guo; Hanbo Guo; Shichao Wang; Lifeng Pan (Proceedings of the National Academy of Sciences, 2025)
NCOA4, a dedicated autophagy receptor for mediating selective autophagy of ferritin (ferritinophagy), plays a vital role in maintaining cellular iron homeostasis. The cellular abundance of NCOA4 is regulated by the E3 ligase HERC2 that can specifically target NCOA4 for proteasomal degradation under iron-replete conditions. However, the detailed molecular mechanism governing the iron-dependent recognition of NCOA4 by HERC2 remains elusive. Here, using multidisciplinary approaches, we systematically characterize the HERC2-binding domain (HBD) of NCOA4 and its interaction with HERC2. We uncover that NCOA4 HBD harbors a [2Fe-2S] cluster and can exist in two different states, the apo -form state and the [2Fe-2S] cluster–bound state. Moreover, we unravel that HERC2 can effectively recognize the [2Fe-2S] cluster–bound NCOA4 HBD through its Cullin-7-PARC-HERC2 (CPH) domain and iron–sulfur cluster–dependent NCOA4-binding domain (INBD) with a synergistic binding mode. The determined crystal structures of HERC2(2540-2700) and its complex with the [2Fe-2S] cluster–bound NCOA4 HBD together with relevant biochemical and cellular results not only elucidate how NCOA4 HBD specifically senses cellular iron level by binding a [2Fe-2S] cluster but also reveal the molecular basis underlying the specific interaction of HERC2 with the [2Fe-2S] cluster–bound NCOA4 HBD. In summary, our findings provide mechanistic insights into the iron-dependent turnover of NCOA4 by HERC2 and expand our understanding of the regulatory mechanism of NCOA4-mediated ferritinophagy.